Effect of conservation tillage practices on rice fallow sunflower (Helianthus annuus L.) at Odisha: Effect of conservation tillage practices on rice fallow sunflower (Helianthus annuus L.) at Odisha - ANITA MAHAPATRA,; DIKSHA PATEL,; K RAMESH,; BISHNUPRIYA GOUDA, (Journal of Oilseeds Research, 2020)
Sunflower is an emerging profitable rice fallow crop at Odisha. An experiment at College of Agriculture(OUAT) Bhubaneswar on rice fallow sunflower conducted to standardize tillage, fertilizer dose and suitable hybrid has shown that sunflower hybrid KBSH 44 performed better than other hybrids under zero tillage at 150% RDF and registered the maximum nutrient uptake.